ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN MODEL ALTMAN Z SCORE PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sartika, Umi (Balance : Jurnal Akuntansi dan Bisnis, 2017)
ABSTRACTThe aim of this research is to test whether the altman model (z score) could be used to predict bankruptcy in the public companies in Indonesia Stock Exchange. Altman  z score is one of the multivariate analysis-model which is useful to predict the company bankruptcy with the trusted accuracy level. This sample selection was done by purposive judgement sampling method. The sample used was 16 companies from all public company listed in the Indonesia Stock Exchange (IDX) periode 2012-2016. While the source of this research data was collected from the company financial reporting in Indonesia Stock Exchange (IDX). The data was processed by the method of the z score formula Z = 1,2X1 + 2,4X2 + 3,3X3 + 0,64X4 + 1,0X5. With the description of Z <1,81 the company categorized into companies that will be bankrupt, the value Z 1,81< 2,99 then the company is considered to be in the grey area of bankrupt enterprises the possibility area and some are not, and the value  of Z  > 2,99 the the company is is a very healthy state so that the probability of bankruptcy is very little going on. The result of this research shows that almost of the public companies are in the bankrupt position with the different bankruptcy level